ANALYSIS OF DISRUPTIVE INNOVATION IMPLEMENTATION STRATEGY - Anggasta, Astrid Giovani; Kusumawardhani, Amie (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Increased digitization and automation in the construction industry can trigger the emergence of a disruptive innovation phenomenon. Incumbent companies that previously dominated the market may collapse if they are unaware of the disruption phenomenon. Although technology is a key factor in development and innovation, accurate business strategy is needed to manage disruptive innovation so that it can become a new advantage for the company. This study aims to classify PT Pembangunan Perumahan Tbk’s disruptive innovation implementation strategy into ideation, incubation, and scaling, and its impact to the company's innovation performance. This study used qualitative research method with case study approach. Data was collected using in-depth interviews with senior manager and senior officer from the Strategic Planning, Research and Technology Division of PTPP and documentation analysis. The result of the research shows that PTPP performs ideation, incubation, and scaling, and able to balance exploration and exploitation in implementing disruptive innovation. The increase in innovation performance based on financial metrics is analyzed from the increase in revenue and profitability. Meanwhile, based on non-financial metrics, innovation performance is measured based on the significance of added value provided by innovation, life cycle improvement, learning organization improvement, and response to dynamic markets. Keywords: disruptive innovation, disruption, strategy, construction